NILAI CERPEN MEMEDI SATAK DUKUH, TONYO, DAN LEAK RARE DALAM PUPULAN CERPEN MACAN RADEN KARYA I GUSTI PUTU BAWA SAMAR GANTANG - Rimbawa, Arisana (Humanis; Volume 12. No.1. Juli 2015)
This study aims to describe and reveal the structure of the narrative which builds stories Memedi Satak Hamlet , Tonyo , and Leak Rare . In addition , this study also aims to determine the social values embodied in the stories Memedi Satak Hamlet , Tonyo , and Leak Rare . This study uses a structural theory according Teeuw (1984 ) and the value according Koentjaraningrat (1979 : 204 ) . Methods and techniques in this study were divided into three stages , namely the stage of providing data using methods refer to techniques supported by translation and recording techniques . Stage of data analysis using descriptive qualitative analytic techniques . Stage presentation of results of data analysis using informal methods supported by deductive and inductive techniques . The results obtained in this study is to reveal the structure of the narrative that builds stories Memedi Satak Dukuh , Tonyo , and Leak Rare include : Incident , plot , setting , character and characterization , theme and mandate . The flow in this Raden Tigers pupulan short story using straight grooves to form an interwoven stories intact . Background background includes place, time , and atmosphere . The main character in the short story of Hamlet is glazed Memedi Satak Unfortunately , the secondary characters are Aji Tambun , complementary figure is wife Aji Tambun ( Prickly Santi ) , Mangku Natrang , and Satak Villagers Hamlet . The main character in the short story is Tonyo Si I , is the mother of the secondary characters I , the main character in a short story is a Rare Leak Si I , is the wife of the secondary characters I , the complementary character is mBok Opong . The theme of the short story of Hamlet is Memedi Satak abduction by Memedi ( supernatural beings ) , the theme of the short story is the existence Tonyo Tonyo ( supernatural beings ) , the theme of the short story is the battle against Leak Leak Rare Rare ( supernatural beings ) , the mandate of short stories Satak Memedi Hamlet , Tonyo , and Leak Rare is the existence of supernatural beings / noetic which are side by side with human existence and therefore we as religious people especially the hindu religion must believe in the existence of the scale ( real ) and the timeless nature ( not real ) and therefore we must be alert to the existence of supernatural beings is to avoid things that are not desirable . In the study of literature revealed four values of social values that include the value of religion / religious , ethics / morality , loyalty value , psychological value